The Influence of Grit and Self-Regulated Learning on English Academic Achievement with Family Support as a Moderating Variable - Zulfa, Indana; Mulyono, Rachmat (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to analyze the influence of grit and Self-Regulated Learning (SRL) on students' academic achievement in English, with family support as a moderating variable. The research employed a quantitative method with a path analysis design. The sample consisted of 186 randomly selected middle school students. The research instruments included grit scales, SRL scales, and family support questionnaires, all of which were validated and reliable. The results showed that Grit (X1) had a positive and significant effect, as indicated by a significance value of 0.000 < 0.05 or a t-value > t-table (5.947 > 1.653). Similarly, the Self-Regulated Learning variable showed a positive and significant effect with a significance value of 0.000 < 0.05 or a t-value > t-table (7.158 > 1.653). Simultaneously, the combined influence of grit and Self-Regulated Learning on English academic achievement was positive and significant, as demonstrated by an F-value > F-table (31.358 > 3.05). According to the model summary table, the R-Square value was 0.255, indicating that grit and Self-Regulated Learning contributed 25.5% to English academic achievement, while the remaining 74.5% was influenced by other factors not examined in this study. The interaction coefficient of Grit with Family Support showed a negative but insignificant effect (p > 0.05) or a t-value < t-table (-1.643 < 1.653). This means that Family Support as a moderator was not significant in moderating the relationship between Grit and Academic Achievement. The negative value indicates that Family Support weakens the influence of Grit on Academic Achievement. Similarly, the interaction coefficient of Self-Regulated Learning with Family Support showed a negative and insignificant effect (p > 0.05) or a t-value < t-table (-1.309 < 1.653). This indicates that Family Support does not moderate (or weakens) the relationship between Self-Regulated Learning and Academic Achievement. The conclusion of this study emphasizes the importance of developing grit and SRL through educational approaches and optimizing the role of families in supporting students' academic success.